From active to stable: Paraglacial transition of Alpine lateral moraine slopes. (1st October 2018) - Eichel, Jana; Draebing, Daniel; Meyer, Nele
Abstract: Many retreating Alpine valley glaciers leave large lateral moraines behind. Reworking of these landforms by geomorphic processes is one of the most important paraglacial processes in many Alpine environments. Although several studies investigated moraine reworking by gullying processes, it is not well known what happens when gullying ceases and why and when lateral moraine slopes become stable. This study improves the understanding of the paraglacial transition from active to stable Alpine lateral moraine slopes by assessing potential influencing factors, indicators for completed paraglacial adjustment, and its spatiotemporal patterns using a combination of geomorphic and ecologic data. A geomorphic and ecologic permanent plot survey and geomorphic mapping were carried out on three lateral moraine complexes in the Turtmann glacier foreland (Switzerland). Subsequently, permanent plot data were analysed using multivariate statistics. Our study suggests that ecosystem engineering by colonizing plant species, slope geomorphometry, and material properties are important factors influencing the paraglacial transition from active to stable slopes. Geomorphic processes are often absent once vertical vegetation layers and soil horizons develop, showing that mature vegetation and advanced soil development are valuable indicators for slope stability and completed paraglacial adjustment. In a conceptual model, we describe the paraglacial transition of Alpine lateral moraine slopes as a temporal sequence in which gullying (Stage I), solifluction (Stage II), and finally stabilization (Stage III) follow one after another. In space, paraglacial adjustment is heterogeneous, and resulting patterns can be explained by the identified influencing factors.